Literatura exilului - Nicoleta Sălcudeanu (Revista de Istorie și Teorie Literară)
The article opens with a short history of the Romanian literary exile. Then it focuses on the specificities of the Romanian exile after the World War II: the long duration of it, the loss of hope for returning to the natal country, the multiple reasons for (self)-exile, grouping around polarity centers such as radios, magazines, literary circles, etc., the small number of dissidents and the fact that the Romanian exile did not promoted Romanian literature for the foreign countries, but limited itself to address exclusively to Romanians for a political purpose. A detailed analysis is dedicated to the cultural pillars with real impact on the Romanian exile (cultural societies and literary circles, literary and cultural newspapers published, Free Europe Radio Post, dissidents). Important institutions of exile are also described: Romanian Center for Researches in Paris, “Carol I” Royal University Foundation in Paris, Romanian Library in Freiburg, Romanian Academic Society in Roma, Romanian-Spanish Foundation in Madrid, The American Romanian Academy of Arts and Sciences, The Free Romanians League and other associations and cultural centers around the world.